Discovery of the mineral brucite (magnesium hydroxide) in the tropical calcifying alga Polystrata dura (Peyssonneliales, Rhodophyta). Issue 3 (18th May 2015) - Nash, Merinda C.; Russell, Bayden D.; Dixon, Kyatt R.; Liu, Minglu; Xu, Huifang; Graham, M.
<x xml:space="preserve">Abstract</x> Red algae of the family Peyssonneliaceae typically form thin crusts impregnated with aragonite. Here, we report the first discovery of brucite in a thick red algal crust ( 1 cm) formed by the peyssonnelioid species Polystrata dura from Papua New Guinea. Cells of P. dura were found to be infilled by the magnesium‐rich mineral brucite [Mg(OH)2]; minor amounts of magnesite and calcite were also detected. We propose that cell infill may be associated with the development of thick (> 5 mm) calcified red algal crusts, integral components of tropical biotic reefs. If brucite infill within the P. dura crust enhances resistance to dissolution similarly to crustose coralline algae that infill with dolomite, then these crusts would be more resilient to future ocean acidification than crusts without infill.